Using of modified symmetry principle of the structural schemes for automatic control systems synthesis - Шеремет, Олексій Іванович; Садовой, Олександр Валентинович (Eastern-European Journal of Enterprise Technologies, 2016)
The solution of inverse dynamic problems using the symmetry principle of structural schemes can be a basis for the synthesis of automatic control systems of technical objects. This approach requires compensation of the dynamic properties of the control object. Most scientific papers idealize the object, that is assume that its dynamic characteristics can be fully compensated by controllers. The impact of transfer functions of modifying links on dynamic and static characteristics of automatic control systems is also understudied. The possibility of using methods for solving inverse dynamic problems for the synthesis of automatic control systems of technical objects is investigated. The mathematical modeling confirmed that ideal tracking of inputs under the full compensation of dynamic properties of the control object is impossible in real systems. The rules, which allow determining the inverse model of the control object directly by its structural scheme in the first canonical controllability form, without having to convert differential equations, are formulated. The modified symmetry principle of the structural schemes, which lies in introducing the integrating link to a direct branch of the closed system, which is included consistently with the inverse model, and provides formation of achievable dynamic characteristics desired with a limited gain is developed.